The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1063/1.347118
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of molecular-beam epitaxially grown CdTe on GaAs by x-ray photoelectron spectroscopy

Abstract: X-ray photoelectron spectroscopy studies of CdTe-GaAs interfaces are reported. The growth start of CdTe on GaAs can be nearly stoichiometric if convenient growth parameters are chosen. The valence-band offset between these two materials is found to be large (470 meV). Cd-Te-metal-GaAs multilayers have been grown with very thin metal films. The CdTe-GaAs band offset is not influenced by such intermediary metal layers. The experimentally obtained value for the valence-band offset is compared with recent theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…The Te/M ratio evolved with the similar tendency as that of the film deposited by CSS, which was 2.5 [21]. In a CdTe film deposited by MBE on GaAs at the substrate temperature of 563 K, Waag et al [14] found that the Te/M ratio was below 40/60 when the film thickness was less than 10 Å and it approached to 1 as the film being thickened. The base pressures during deposition of these films via different methods vary from ultrahigh (MBE), middle (VE), to low vacuum conditions (CSS); the substrate temperatures vary from room temperature (VE) to over 800 K (CSS), and the source-substrate distances vary from a few millimeters (CSS) to dozens of millimeters (VE).…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…The Te/M ratio evolved with the similar tendency as that of the film deposited by CSS, which was 2.5 [21]. In a CdTe film deposited by MBE on GaAs at the substrate temperature of 563 K, Waag et al [14] found that the Te/M ratio was below 40/60 when the film thickness was less than 10 Å and it approached to 1 as the film being thickened. The base pressures during deposition of these films via different methods vary from ultrahigh (MBE), middle (VE), to low vacuum conditions (CSS); the substrate temperatures vary from room temperature (VE) to over 800 K (CSS), and the source-substrate distances vary from a few millimeters (CSS) to dozens of millimeters (VE).…”
Section: Resultsmentioning
confidence: 72%
“…Interfacial composition and structural properties play very important parts in thin film growth and the final device performance [14][15][16][17][18][19]. A thorough understanding of the interfaces between CdZnTe films and the substrates will help with improving the film quality and further advancing their applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of in situ x-ray photoelectron spectroscopy (XPS) helped to ensure that only optimally cleaned surfaces were used in the following investigations. 18,19 A RIBER model CER 606 electron gun with model ACE 1010 controlling electronics was used as a source of high-energy electrons both for the RHEED patterns and in the investigations of the effects of high-energy electrons on the epitaxial growth surfaces. In the present experiments, the acceleration voltage of the electron gun was about 9 kV, the electron current was about 20 j1A, and the beam was focused as small as possible.…”
Section: Methodsmentioning
confidence: 99%
“…Table 2) thus showing that a number of substrates do not fulfill the requirement of a high resistivity. Also, the structural quality is often not quite satisfactory [27]. The values of the conductivity O"E of the epitaxial layers compiled in Table 2 were determined at room temperature by the van der Pauw method [28] which is fairly reliable for our samples which all are n-type.…”
Section: Analysis Of the Experimental Datamentioning
confidence: 99%